ANALISIS KINERJA KEUANGAN KOPERASI DAN PENGARUHNYA TERHADAP PERSEPSI TRANSPARANSI DAN KEPUASAN ANGGOTA PADA KOPERASI KARYAWAN SMP NEGERI 4 CILEUNGSI JAWA BARAT - Halimah, Zahra Nabila Azizah; Ade Onny Siagian (Jurnal Bisnis Terapan, 2026)
This study aims to analyze the influence of financial management capabilities and the transparency of profit-sharing (Sisa Hasil Usaha/SHU) distribution on cooperative member satisfaction using the Expectation Confirmation Theory (ECT) approach. ECT is applied to understand the extent to which member expectations and perceptions are confirmed after receiving the cooperative’s financial performance outcomes, particularly in financial management and SHU distribution. This research adopts a mixed method approach, combining qualitative descriptive analysis to explore the cooperative’s general condition and member perceptions, and quantitative analysis using the Pearson Product Moment correlation test to measure the relationship between variables. The object of this study is the Employee Cooperative of SMPN 4 Cileungsi, utilizing financial report data from 2021 to 2024 and member questionnaire results. The findings show that the cooperative’s financial performance is categorized as excellent, with a three-year average Return on Assets (ROA) of 6.55%, Return on Equity (ROE) of 7.65%, Current Ratio of 3.68x, and Debt to Equity Ratio (DER) of 0.19. The Pearson correlation test resulted in r = 0.94, indicating a very strong relationship between financial management and SHU distribution transparency with member satisfaction. These findings highlight the importance of sound financial practices and transparency as key factors in building member trust and satisfaction in cooperatives as economic institutions.